TEACHER READINESS IN FACING COURAGEOUS LEARNING DURING THE COVID-19 PANDEMIC - Herlina; Basri; Yusuf (SMART: Journal of Multidisciplinary Educational, 2024)
This research aims to find out how prepared teachers are in facing online learning during the Covid-19 pandemic at SMP Negeri 3 Palakka, Bone Regency. The type of research used is quantitative research. The data obtained was analyzed descriptively statistically through frequency tables. Based on the research results, it can be concluded that teacher readiness in facing online learning during the Covid-19 pandemic at SMP Negeri 3 Palakka is in the high readiness category. This is in accordance with the results of the data recapitulation which consists of five indicators, of which there is one indicator in the Sufficient category, namely the indicator of technology use. Meanwhile, indicators in the high category are four indicators, namely curriculum indicators, lesson plans, teaching materials and infrastructure.